A harmonized and coordinated assessment of the abundance and composition of seafloor litter in the Adriatic-Ionian macroregion (Mediterranean Sea). (February 2019) - Fortibuoni, Tomaso; Ronchi, Francesca; Mačić, Vesna; Mandić, Milica; Mazziotti, Cristina; Peterlin, Monika; Prevenios, Michael; Prvan, Mosor; Somarakis, Stelios; Tutman, Pero; Varezić, Dubravka Bojanić; Virsek, Manca Kovac; et al.
Abstract: Marine litter is a threat to marine life and an economic burden for coastal communities, but efforts to address the issue are hampered by the lack of data for many countries. We performed the first harmonized assessment of seafloor litter (trawl and visual surveys) in six countries of the Adriatic-Ionian macroregion. Seafloor litter showed an uneven distribution throughout the area, with large differences in litter densities and composition among countries and locations. An emerging problem in the area resulted in short-term & single-use objects that represented the largest fraction of litter. Packaging was the economic sector contributing most to seafloor litter on the continental shelf and upper slope, while in some areas aquaculture (mussel farming) represented a key activity producing marine litter. In coastal areas and bays (e.g. Boka Kotorska bay, Montenegro), seafloor litter was mainly related to construction activities and electronic goods, which are a consequence of fly-tipping/illegal dumping. Highlights: First assessment of seafloor litter (3–281 m) in the Adriatic-Ionian macroregion First data on seafloor litter in Slovenia, Croatia and Bosnia & Herzegovina The distribution of marine debris is uneven both at country and local level. Single-use plastic items are the large majority of litter found. Mussels farming locally represents a major contributor to seafloor litter.